KETERKAITAN USIA, JENIS KELAMIN, DAN TINGKAT RELIGUITAS TERHADAP PENERAPAN GAYA KEPEMIMPINAN - Widhi Ariestianti R (Jurnal Manajerial, 2019)
The purpose of this study to analyze the influence of age, sex and religiousity on leadership style. Dependen variabel in this research is leadership style and independen variabel in this research are sex, age and religiousity. The samplein this study are worker who have subordinate to do dialy job. The method use is the multiple linier analysis regresion. The result of thi study indicate that age, sex and religousity have direct influence on leadership style. Age has dominan influence on leadership style, and than religiousty has secound dominan influence on leadership style. Sex has little influence on leadership style. From this analysis can be know that whatever gander of leader as long as more spiritual experince, more mature person is shown by life experince they owen, they will more wise in applying leadersip style. Leader will support their subordinate for improve their self potential.